Pengaruh Motivasi Siswa, Fasilitas Belajar, dan Kedisiplinan Belajar Siswa terhadap Hasil Bela-jar (Studi Pada Siswa Kelas X SMA Negeri 5 Pamekasan) - Agung Suprianto; Rihana Rihana (Jurnal Penelitian dan Pendidikan IPS, 2021)
Abstract Student learning outcomes are a manifestation of the success of the teaching and learning process in educational institutions. The objectives of this study are 1) to analyze the influence of learning motivation on learning outcomes with control facilities and student discipline 2) to analyze the influence of facilities, learning motivation, and discipline together on student learning outcomes. 3) Analyzing the differences in achievement based on the background of the science and social studies majors of Class X students in the Science subject at SMA Negeri 5 Pamekasan. The form of research design is descriptive quantitative in the form of explanation. The population in the study was students of Class X Science Subject SMA Negeri 5 Pamekasan with a total sample of 39 students with a random sampling technique. The data collection method is a questionnaire and documentation method. The data analysis technique used partial and multiple regression with ANOVA model assisted by the computer program SPSS version 18.00. The results illustrate the effect of learning motivation on learning outcomes by showing that learning motivation has a significant effect on learning outcomes. Analyze the influence of facilities, learning motivation, and discipline together on student learning outcomes. The hypothesis that says there is a significant effect of Learning Facilities on Learning Outcomes is accepted. This means that learning facilities have a significant relationship with learning outcomes. Analyzing the difference in achievement based on the background of the science and social studies majors, the calculation obtained the t-count between the science learning outcomes and the social studies learning outcomes, which shows that t count = 118.625. While the t table (α = 0.05; db residual = 37) is 77.006. because t count> t table, namely 77.006> 2.857, the science class students are higher than the social studies at 81.289. Keywords: motivasi, fasilitas, kedisiplinan belajar, prestasi belajar